2007
DOI: 10.1073/pnas.0702010104
|View full text |Cite
|
Sign up to set email alerts
|

Four domains of p300 each bind tightly to a sequence spanning both transactivation subdomains of p53

Abstract: The transcriptional coactivator p300 binds to and mediates the transcriptional functions of the tetrameric tumor suppressor p53. Both proteins consist of independently folded domains linked by intrinsically disordered sequences. A well studied short sequence of the p53 transactivation domain, p53(15-29), binds weakly to four folded domains of p300 [Taz1/cysteine-histidine-rich region 1 (CH1), Kix, Taz2/CH3, IBiD], with dissociation constants (K D) in the 100 M region. However, we found that a longer N-terminal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
241
4
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 192 publications
(263 citation statements)
references
References 53 publications
15
241
4
1
Order By: Relevance
“…It has been shown that p53 interacts with the Taz1, Kix, Ibid and Taz2 domains and probably with the IHD domain (Teufel et al, 2007). The strongest binding of unphosphorylated p53 was observed to the Taz2 domain.…”
Section: Introductionmentioning
confidence: 81%
“…It has been shown that p53 interacts with the Taz1, Kix, Ibid and Taz2 domains and probably with the IHD domain (Teufel et al, 2007). The strongest binding of unphosphorylated p53 was observed to the Taz2 domain.…”
Section: Introductionmentioning
confidence: 81%
“…It clearly consisted of two separate subdomains that may be defined as TAD1 from residues 10-31 and TAD2 from residues 46-67, unlike p53, where TAD1 and TAD2 correspond to residues 1-40 and 41-60, respectively (11). There is a linker between TAD1 and TAD2, broadly corresponding to Q33-G45.…”
Section: Resultsmentioning
confidence: 99%
“…The site of interaction between the KIX domain and both p53-TADs corresponds with the annotated 9aaTADs and the TAF9 binding site (NMR data, eight out of nine annotated amino acids). Despite the unrecognizable sequence similarity (Table 2 and 3) 4,7 , both p53-TAD1 and p53-TAD2 share the same docking sites on the KIX domain, which may result from the presence of a common motif in the p53 transactivation domains, the 9aaTAD 8 . p53 and further well characterized 9aaTAD-transcription factors, which interact with CBP-p300 and other general co-activator GCN5 are listed in Table 3.…”
mentioning
confidence: 99%
“…Interestingly, CBP-p300 domains KIX, TAZ1, TAZ2 and IBiD are also able to bind p53-9aaTAD1 4,7 ( Table 2). The site of interaction between the KIX domain and both p53-TADs corresponds with the annotated 9aaTADs and the TAF9 binding site (NMR data, eight out of nine annotated amino acids).…”
mentioning
confidence: 99%
See 1 more Smart Citation